Fundoscopic Comparison of Retinal Hemorrhages After Retinal Venous Occlusion in Patients with Diabetic Mellitus (Medical Forum Monthly, 2021)
Objective: To compare variability of retinal hemorrhages at fundoscopy after retinal vein occlusion in patients with Diabetes Mellitus.Study Design: A cross-sectional studyPlace and Duration of Study: This study was conducted at the Sindh Institute of Eye Hospital, Hyderabad from 1st January 2019 to 31 December 2019.Materials and Methods: There are 89 patients aged 30 to 70 years or more, both male and female in this study. Patients with newly diagnosed central retinal occlusion were included. Diabetes mellitus was verified in 89 of the patients, and they were all under the age of 35 when they were treated. Utilizing Slit Lamp photography and a close examination of the fundus of a 90 D Volk Lens (RETINAL CAMERA-TRC-50EX). Initiated by the scientists, and later confirmed by an expert ophthalmologist, their ultimate diagnosis was correct. Version 20 of the Stata statistical programme for social science has been entered and tested by the researchers.Results: A total of 89 diabetics with retinal vein occlusion (RVO) had fundoscopy. Patients ranged in age from 54.93 years old on average plus 8.854 years on the standard deviation (33 to 70 years). In this study, there were somewhat more women than men: 46 women (51,6%) and 43 men (48.31 percent ).We found a link between retinal haemorrhage and diabetes mellitus in patients with retinal vein blockage in this study. Dot blot haemorrhages occurred in 37 diabetic patients, while flame formation haemorrhages occurred in 29 diabetic patients.Conclusion: This research concluded that in patients with retinal vein occlusion (RVO) associated with diabetes mellitus a large number of different forms of retinal hemorrhogen is present. It has been shown that dot blot haemorrhages are correlated with diabetes or high pressure in both the retinal vein occlusion, although in diabetic patients they were significantly higher. In retinal vein occlusions with diabetes, flame-like bloods were also observed but were more frequent in diabetic patients.